Techniques and Applications for Mobile Commerce. - Branki, Cherif (IOS Press, 2008)
Mobile Commerce (M-Commerce) comprises applications and services that are accessible from Internet-enabled mobile devices. It involves new technologies, services, and business models. While it is different from traditional e-Commerce it can also be seen as an extension of e-Commerce in the sense that it, among others, makes e-Commerce available in a modern way to new application areas and to a new set of customers. The Internet is on its way to leave traces in all aspects of our life independently of where we are. Already today, mobile phones and PDAs become an indispensable part of our life a.